HER Voice Newsletter Edition 2, April 2024 - Awinoh, Martha (CGIAR Initiative on Gender Equality, 2024)
The second edition of HER Voice showcases the recent research endeavors by the HER+ Gender Equality Research Initiative in collaboration with our partners across twelve countries in sub-Saharan Africa and South Asia. In light of our goals of increasing gender equality and supporting the capabilities of all, including women, to thrive and contribute to vibrant and resilient communities, we continued investigating the structural constraints that hinder gender equality and climate resilience in food, land and water systems and developing innovative approaches to address these constraints. The four Work Packages (WPs) of HER+ focus on addressing constraints that relate to gender norms (WP TRANSFORM) and gender unequal voice and influence in governance and decision-making (WP VOICE), as well as unequal access to and control over resources (WP PROTECT) and limited agency (WP EMPOWER).